REALISASI TINDAK KESANTUNAN KOMISIF DI KALANGAN MASYARAKAT PEDAGANG PASAR TRADISIONAL SUNGAI PINANG DESA MEKARPURA KABUPATEN KOTABARU - Sri Juniati (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2019)
The purpose of this study was (1) to describe the principle of politeness in commissive politeness acts in the Sungai Pinang traditional market merchant community in Mekarpura Village, Kotabaru Regency (2) to describe the form of commissive politeness in the traditional Pinang river market merchant community in the Mekarpura village, Kotabaru Regency. This type of research is qualitative descriptive in which the data collected are in the form of words, pictures, and not numbers. That was caused by the application of qualitative methods. Sources of data in conducting this research are primary data and secondary data. Data collection techniques in this study by observation, record, and documentation. And data analysis techniques are data recording transcripts, pragmatic matching techniques, data classification, data analysis and finally draw conclusions. The results of the study showed that the principle of politeness in commissive politeness behavior among the traditional market traders of Sungai Pinang Village, Mekarpura Village, Kotabaru Regency was the use of wisdom maxim and acceptance maxim. And the form of commissive politeness among the traditional market traders of Sungai Pinang, Mekarpura Village, Kotabaru Regency, namely the use of commissive speech acts promised, commissive speech acts threatened and commissive speech acts offered. Keywords: Realization, Commitment Politeness, Traditional Trader